2016
DOI: 10.1620/tjem.239.89
|View full text |Cite
|
Sign up to set email alerts
|

Successful Glycemic Control Decreases the Elevated Serum FGF21 Level without Affecting Normal Serum GDF15 Levels in a Patient with Mitochondrial Diabetes

Abstract: Mitochondrial diabetes mellitus is a subtype of diabetes linked to mutations in mitochondrial DNA. In patients with mitochondrial diabetes mellitus, the effect of glycemic control on the serum concentrations of fibroblast growth factor 21 (FGF21) and growth differentiation factor 15 (GDF15) has not been evaluated. FGF21 and GDF15 have been reported to be useful biomarkers for the diagnosis and severity assessment of mitochondrial diseases like mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Serum levels of GDF15 were found to be higher in prediabetes/T2DM patients than in healthy volunteers and independently associated with CV risk scores [124], body mass index, waist-to-hip ratio [125], insulin resistance [126], hs-CRP [127] and parameters of glucose metabolism (C-peptide, fasting pre-hepatic beta cell function, impaired fasting glucose) [128,129], while successful glycemic control did not cause a decrease in GDF15 levels [130].…”
Section: Growth Differentiation Factor 15mentioning
confidence: 96%
“…Serum levels of GDF15 were found to be higher in prediabetes/T2DM patients than in healthy volunteers and independently associated with CV risk scores [124], body mass index, waist-to-hip ratio [125], insulin resistance [126], hs-CRP [127] and parameters of glucose metabolism (C-peptide, fasting pre-hepatic beta cell function, impaired fasting glucose) [128,129], while successful glycemic control did not cause a decrease in GDF15 levels [130].…”
Section: Growth Differentiation Factor 15mentioning
confidence: 96%
“…However, there are severe controversies in this issue, because few reports in opposite revealed that lowered GDF-15 levels are beneficial against endothelial injury and microvascular inflammation [35,36]. In contrast, there is evidence that successful glycemic control and treatment of dyslipidemia with statins in moderate-to-high doses did not cause changes in plasma levels of GDF-15 [37,38]. Although traditionally achieving of full control for hyperglycemia and hyperlipidemia is considered a predictor of better clinical outcomes in people with diabetes, lack of GDF-15 dynamic requires to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Both are considered as mitokines induced in response to mitochondrial but also ER stress and other cellular stress situations in various organs and tissue; and both have been demonstrated to exert systemic metabolic effects [12,14,45]. FGF21 and GDF15 are used as biomarkers for the diagnosis and severity assessment of mitochondrial diseases including mitochondrial myopathy, [46,47], but they were also shown to be elevated in patients with different inherited metabolic diseases that are not restricted to mitochondrial disorders [48]. Interestingly, circulating FGF21 and in particular GDF15 increase with aging, and both have been suggested as markers of biological age in humans [49].…”
Section: Induction Of Mitokines By Mitochondrial Dysfunctionmentioning
confidence: 99%